The first human induced pluripotent stem cell line of Kashin–Beck disease reveals involvement of heparan sulfate proteoglycan biosynthesis and PPAR pathway. (6th August 2021) - Liu, Huan; Wu, Cuiyan; Zhao, Hongmou; Zhang, Feng'e; Zhao, Guanghui; Lin, Xialu; Wang, Sen; Wang, Xi; Yu, Fangfang; Ning, Yujie; Yang, Lei; Liu, Peilong; et al.
Abstract : Kashin–Beck disease (KBD) is an endemic osteochondropathy. Due to a lack of suitable animal or cellular disease models, the research progress on KBD has been limited. Our goal was to establish the first disease‐specific human induced pluripotent stem cell (hiPSC) cellular disease model of KBD, and to explore its etiology and pathogenesis exploiting transcriptome sequencing. HiPSCs were reprogrammed from dermal fibroblasts of two KBD and one healthy control donor via integration‐free vectors. Subsequently, hiPSCs were differentiated into chondrocytes through three‐week culture. Gene expression profiles in KBD, normal primary chondrocytes, and hiPSC‐derived chondrocytes were defined by RNA sequencing. A Venn diagram was constructed to show the number of shared differentially expressed genes (DEGs) between KBD and normal. Gene oncology and Kyoto Encyclopedia of Genes and Genomes annotations were performed, and six DEGs were further validated in other individuals by RT‐qPCR. KBD cellular disease models were successfully established by generation of hiPSC lines. Seventeen consistent and significant DEGs present in all compared groups (KBD and normal) were identified. RT‐qPCR validation gave consistent results with the sequencing data. Glycosaminoglycan biosynthesis—heparan sulfate/heparin; PPAR signaling pathway; and cell adhesion molecules (CAMs) were identified to be significantly altered in KBD. Differentiated chondrocytes derived from KBD‐origin hiPSCs provide the first cellular disease model for etiological studies of KBD. This study also provides new sights into the pathogenesis and etiology of KBD and is likely to inform the development of targeted therapeutics for its treatment. Abstract : Differentiated chondrocytes derived from KBD‐origin hiPSCs provide the first cellular disease model for etiological studies of KBD, which will enable further understanding of KBD. We investigated the pathogenesis of KBD using transcriptome sequencing of hiPSC‐derived chondrocytes and primary chondrocytes. Dysregulated mRNAs in KBD were identified to contribute to the pathogenesis of KBD by regulating GAG biosynthesis—heparan sulfate/heparin; PPAR signaling pathway; and CAMs.